Effects of Late Sodium Current Blockade on Ventricular Refibrillation in a Rabbit Model. (March 2017) - Azam, Mohammed Ali; Zamiri, Nima; Massé, Stéphane; Kusha, Marjan; Lai, Patrick F.H.; Nair, Govind K.; Tan, Nigel S.; Labos, Christopher; Nanthakumar, Kumaraswamy
Abstract : Background—: After defibrillation of initial ventricular fibrillation (VF), it is crucial to prevent refibrillation to ensure successful resuscitation outcomes. Inability of the late Na + current to inactivate leads to intracellular Ca 2+ dysregulation and arrhythmias. Our aim was to determine the effects of ranolazine and GS-967, inhibitors of the late Na + current, on ventricular refibrillation. Methods and Results—: Long-duration VF was induced electrically in Langendorff-perfused rabbit hearts (n=22) and terminated with a defibrillator after 6 minutes. Fibrillating hearts were randomized into 3 groups: treatment with ranolazine, GS-967, or nontreated controls. In the treated groups, hearts were perfused with ranolazine or GS-967 at 2 minutes of VF. In control experiments, perfusion solution was supplemented with isotonic saline in lieu of a drug. Inducibility of refibrillation was assessed after initial long-duration VF by attempting to reinduce VF. Sustained refibrillation was successful in fewer ranolazine-treated (29.17%; P =0.005) or GS-967–treated (45.83%, P =0.035) hearts compared with that in nontreated control hearts (84.85%). In GS-967–treated hearts, significantly more spontaneous termination of initial long-duration VF was observed (66.67%; P =0.01). Ca 2+ transient duration was reduced in ranolazine-treated hearts compared with that in controls ( P =0.05) and also Ca 2+ alternans ( P =0.03). Conclusions—: Late Na + current inhibition during long-duration VF reduces the susceptibility to subsequent refibrillation, partially by mitigating dysregulation of intracellular Ca 2+ . These results suggest the potential therapeutic use of ranolazine and GS-967 and call for further testing in cardiac arrest models. Abstract : Supplemental Digital Content is available in the text.